A 1-Year Prospective Analysis of Ice Climbing Injuries. Issue 2 (March 2017) - Runer, Armin; Lampl, Kathrin; Neunhäuserer, Daniel; Runer, Florian; Frick, Nora; Seitlinger, Gerd; Resch, Herbert; Moroder, Philipp
Abstract : Objective: To describe rates, patterns, and causes of acute injuries in an increasingly popular outdoor sport. Design: Prospective cohort study. Setting: One winter season ranging from November 2011 to March 2011. Participants: Seventy ice climbers from 13 different countries and various performance levels. Main Outcome Measures: Participants were asked to complete a monthly Internet-based survey regarding their completed hours of training and competitions and eventual sustained injuries. Results: During 4275 hours of ice climbing, 42 injuries occurred, of which 81.0% were defined as mild, 16.6% as moderate, and 2.4% as severe. The calculated injury rate was 9.8 injuries per 1000 hours of sports exposure. Intermediate ice climbers had a significantly higher injury risk compared with advanced ice climbers (odds ratio, 2.55; 95% confidence intervals, 1.17-5.54; P = 0.018). About 73.8% of all injuries occurred on a frozen waterfall, icicles, or icefalls, whereas 4.8% occurred on artificial ice walls. The head was the most injured body part (47.6%), followed by the knee (14.3%) and the shoulder (11.9%). The most common types of injuries were abrasions (38.1%), contusions (35.7%), and joint sprains (7.1%). Falling ice was the main circumstance leading to injury (59.5%). All athletes with a head injury wore a helmet; however, only 35.0% mentioned they used protective goggles. Conclusion: Ice climbing is a sport with moderate risk for injury with most of the reported injuries being of minor severity. However, severe and fatal injuries, although less common, also occur. Advanced ice climbers with greater experience and skill level have a lower overall injury risk.